Leadership Analysis in Educational Management - Yandri Kusuma, Yanti; Sumianto, Sumianto; Aprinawati, Iis; Ananda, Rizki; Jelita, Lusiana; Desi, Desi Indriyani (The Future of Education Journal, 2026)
This study aims to analyze the leadership of the school principal in managing education at SDN 017 Pulau Lawas. The research focuses on identifying how the principal plans, organizes, implements, and evaluates educational management within the school environment. This study employed a qualitative descriptive method to obtain an in-depth understanding of leadership practices. Data were collected through observation, interviews, and documentation involving the principal and teachers. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results of the study indicate that the principal plays a significant role in improving the effectiveness of educational management through systematic planning, clear division of tasks, coordinated implementation of programs, and continuous evaluation. Supporting factors include leadership competence, collaboration among teachers, and a supportive school environment, while inhibiting factors include limited facilities and external policy constraints. This study is expected to contribute to the development of educational leadership practices and serve as a reference for improving the quality of school management.